Pelaksanaan Restitusi terhadap Anak Penyandang Disabilitas Korban Kekerasan Seksual (Studi di Pengadilan Negeri Kabupaten Madiun) - Mei Hua Pradita; Maria Novita Apriyani (CV Rewang Rencang, 2024)
The right to restitution as a form of legal protection that must be given to child victims of criminal acts. The method used in studying the data is empirical legal with data collection through interviews and literature studies. This study shows the mechanism for fulfilling restitution for children with mental disabilities at the Madiun Regency District Court, and the forms of restitution rights that are entitled to be received by children with mental disabilities who are victims of sexual violence. The fulfillment mechanism at the Madiun Regency District Court has been carried out in accordance with Supreme Court Regulation (PERMA) Number 1 of 2022 concerning Procedures for Settlement of Applications and Granting of Restitution and Compensation to Victims of Criminal Acts